Direct and Derivative Spectrophotometric Determination of Copper(II) and Nickel(II) in Beer, Wine and Edible Oils - V.KIRAN KUMAR,; M. RAMESWARA RAO,; K. B. CHANDRA SEKHAR,; N. DEVANNA, (International Journal of Pharma and Bio Sciences, 2010)
Derivative spectrophotometric determination of copper(II) and nickel(II) based on the formation of their complexes with Diacetylmonoxime-4-hydroxybenzoylhydrazone (DM-4-HBH) reagent has been proposed. Direct and derivative method has been developed for the spectrophotometric determination of micro quantity of Cu(II) and Ni(II) in basic medium. The reagent gives yellowish green and light green coloured complex in pH 10.5 and 9.0 respectively. The maximum absorbance measured at λmax 396 nm and λmax 380 nm for copper(II) and nickel(II) complexes. The molar absorpitivity and sandell’s sensitivity are 1.8 x 104, 2 x 104 L.mol-1.cm-1 and 0.0035, 0.0029 µg.cm-2 respectively. Copper(II) and nickel(II) forms (M:L) 1:1 complex and stability constant of the complexes are 4.2 x 106 and 7.5 x 105 respectively. The derivative amplitude was measured at λmax 433 nm and 404 nm respectively. The developed method was applied for the determination of Cu(II) in Beer, Wine and Ni(II) in edible oil samples.